MEDICINAL PLANTS AS POTENTIAL SOURCE OF ANTIOXIDANT AGENTS: A REVIEW - Ayoub, Zeenat; Mehta, Archana (Asian Journal of Pharmaceutical and Clinical Research, 2018)
All over the world, the recent scientific studies revealed the medicinal properties of plants, which have been examined, because of their effective pharmacological activities, economic viability, and their low toxicity. Reactive oxygen species (ROS) enhancement by endogenous and exogenous stimuli can modify redox circumstances of normal cells. To balance ROS-mediated cellular damage, endogenous antioxidants' protection system subsists; however, when oxidation surpasses the control mechanisms, oxidative stress increases. Detrimental alterations induced in a variety of biomolecules such as proteins, lipids, and DNA which causes chronic escalation of oxidative stresses, which ultimately causes tissue damage and results in numerous diseases. Antioxidants reduce the effects of ROS and help us in the prevention of such diseases. Antioxidants can either be natural or synthetic. Natural antioxidants can be obtained through diet in the form of fruits, spices, vegetables, etc. Synthetic antioxidants such as butylated hydroxytoluene and butylated hydroxyanisole also diminish oxidation, but they have been proved to be dangerous to humankind; therefore, investigation for non-toxic antioxidants has increased in the recent years.